2018
DOI: 10.5812/iranjradiol.55996
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Granulomatous Lobular Mastitis in a Male Breast: A Case Report

Abstract: Idiopathic granulomatous lobular mastitis (IGLM) that mimics breast cancer both clinically and radiologically is a chronic inflammatory condition of the breast without a known etiology. It usually affects childbearing women and is associated with pregnancy, lactation, or use of oral contraceptives. IGLM in a male breast is extremely rare, and only two case reports have been published. A 60-year-old man was referred to our hospital for right breast mass. He had right breast pain with a small palpable lump for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, there are only 16 reported cases of GM in male patients. 1,2,[4][5][6][7][8][9][10][11][12][13][14][15] The reported cases have been summarized in Table 1. We analyzed 12 cases of patients whose characteristics and clinical courses were described.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, there are only 16 reported cases of GM in male patients. 1,2,[4][5][6][7][8][9][10][11][12][13][14][15] The reported cases have been summarized in Table 1. We analyzed 12 cases of patients whose characteristics and clinical courses were described.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 12 cases of patients whose characteristics and clinical courses were described. 2,[6][7][8][9][10][11][12][13][14][15] The median age of the patients at the time of presentation was 46 years (range: 17-60 years). Eight patients (73%) had GM in the right breast, while two (17%) presented with bilateral involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that estrogen stimulation causes the development of acini and lobules in male breasts 2 and might be responsible for the development of GM. Of the 12 cases, four patients had gynecomastia 10,14,15,16 and one was a transgender (male to female transition, receiving estrogen therapy for six years). 2 This supports the fact that GM in males might be associated with abnormal hormonal conditions such as gynecomastia and estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%